Emotional and visual responses to trypophobic images with object, animal, or human body backgrounds: an eye-tracking study - Pengfei Yu; Li Yu; Li Yu; Yuting Li; Cheng Qian; Jia Hu; Weiyi Zhu; Fang Liu; Fang Liu; Qi Wang; Qi Wang; Qi Wang (Frontiers in Psychology)
BackgroundTrypophobia refers to the visual discomfort (e.g., disgust or anxiety) experienced by some people when viewing clusters of bumps or holes. The spectral profile framework suggests that the spectral components of clustered patterns induces trypophobia. In contrast, the cognitive framework speculates that cognitive appraisal of dangerous objects (e.g., ectoparasites) causes trypophobia. A background effect (e.g., more disgust toward trypophobic patterns on the skin than on a desk) seems to support the cognitive framework. However, there is no study providing objective evidence for that effect and verifying these frameworks at the same time. This study aims to address that limitation by psychometric and eye-tracking experiments.MethodsWe recruited 183 participants from colleges. Initially, participants finished a personality questionnaire. The cohort then completed an eye-tracking experiment which showed the trypophobic pattern of lotus seed on three categories of background images (objects, animals and human bodies). Finally, participants rated the image’s disgust and arousal levels using a self-assessment rating scale. Meanwhile, we compared all images’ luminosity and power spectra.ResultsTrypophobic images with the human body or animal backgrounds induced a higher level of disgust and arousal than those with the object backgrounds. Participants gazed faster and dwelled longer at the trypophobic patterns on human body images than on object or animal images. Furthermore, trypophobic images with human body or animal backgrounds induced more substantial pupil dilation than those upon object backgrounds. No significant difference was detected between the power of trypophobic images with human body backgrounds and objects backgrounds. As the trypophobic images with human body backgrounds induced significant emotional or visual responses compared to those with inanimate object backgrounds. Such inconsistent results imply that the differential emotional or visual responses to trypophobic images are probably not induced by the difference in power spectra. Finally, the disgust/arousal level toward trypophobic images did not correlate with personality traits.ConclusionThese results supported the background effect of trypophobia, namely, trypophobic images with animal or human body backgrounds induce more severe disgust and cause more arousal than those with object backgrounds. Our results support the cognitive, but not spectral profile, framework of trypophobia.